Severe pertussis complicated by pulmonary hypertension in a Moroccan infant: a case report - Mehdi Belhakim; Zineb El jaouhahri; Aicha Boudar; Loubna Benaddi; Karima Naanani; Rachida Habbal; Abdelaziz Chlilek (Journal of Medical Case Reports)
Abstract Background Despite high vaccination coverage among children, pertussis continues to pose a significant public health challenge in Morocco. Mortality primarily affects infants under 1 year of age. Although cases of mortality caused by pulmonary hypertension induced by Bordetella pertussis infection have been recorded previously, this complication continues to be relatively uncommon. The main aim of this case report is to raise awareness of this rare but serious complication of pertussis to promote early diagnosis and ensure timely and appropriate therapeutic interventions to improve prognosis. Case presentation A 2-month-old Moroccan girl presented with respiratory distress characterized by paroxysmal, emetic, and cyanotic coughing, followed by noisy inspiratory catch-up. Initial examination revealed a temperature of 38.3 °C, blood pressure of 88/67 mmHg, tachycardia (220 bpm), and tachypnea (70 cpm), with oxygen saturation of 86%. Pulmonary auscultation detected diffuse bilateral rhonchi. Laboratory findings showed leukocytosis (114,000/µL) with neutrophil predominance. Polymerase chain reaction confirmed Bordetella pertussis infection. A thoracic computed tomography scan revealed alveolo-interstitial pneumonia and atelectasis of the middle lobe. Echocardiography indicated pulmonary hypertension (V max, 3.4 m/s; pulmonary artery systolic pressure, 46 mmHg). Treatment included oxygen therapy, clarithromycin, and cephalosporin. Sildenafil was initiated, resulting in respiratory improvement and normalized leukocyte count. Follow-up echocardiogram showed reduced pulmonary artery pressures (V max, 2.7 m/s; pulmonary artery systolic pressure, 32 mmHg). After 25 days, the patient was discharged with asymptomatic status and normal growth and development at 4 months. Conclusion This case report aims to inform practitioners of the rare association between pertussis and pulmonary hypertension. Early diagnosis and aggressive management can improve outcomes and prognosis. This case is a reminder of the complex pathophysiology and therapeutic challenges associated with severe pertussis, underlining the importance of a multidisciplinary approach to optimize the diagnostic and therapeutic management of such patients.